Educational leadership innovation: a recent comprehensive structured review - Mukhtar, Suhaibah; A. Razak, Ahmad Zabidi; Setiyowati, Ninik; Adni, Mohd Azizul (Intelektual Pustaka Media Utama, 2025)
This study provides a systematic review of innovation in educational leadership, a pivotal domain in the dynamic field of educational practices. Despite increasing interest, a comprehensive understanding of how innovation shapes educational leadership and its outcomes remains limited. To address this gap, this review examines studies published up to 2024, retrieved from reputable databases such as Scopus and Web of Science. Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, 33 primary studies were selected for in-depth analysis. The findings are categorized into three key themes: i) digital and technological transformation in education, ii) leadership styles and professional development, and iii) innovative strategies and change management. The review highlights significant advancements in these areas, yet underscores the need for further exploration of their long-term impacts, particularly in diverse educational settings. This work contributes by synthesizing current trends and practices in educational leadership innovation, identifying existing challenges, and proposing pathways for future research. These insights aim to support the development of effective and scalable leadership innovations, ensuring adaptability and impact across various educational environments. This review ultimately serves as a foundation for advancing educational leadership to meet the evolving demands of the 21st-century education landscape.